Building Parameter Analysis with S-UTD-CH model in Multiple Diffraction - Tabakcıoğlu, Mehmet Barış; Ayberkin, Doruk (Ieee, 2015)
Electromagnetic wave propagation models are used in radio planning tool and coverage prediction. These models are based on ray tracing technique or numerical. Slope UTD with convex hull model is a model which has less computation time, higher accuracy of prediction and based on ray tracing technique. S-UTD-CH model is used in multiple diffraction due to that this model gives more accurate results in less computation time. Obstacles can be modelled as knife edge, wedge or cylinder in ultra-high frequencies. inner angle, structure type and relative permittivity constant and conductivity of obstacle and polarization type of electromagnetic wave change the relative path loss at the receiver. In the study, how building parameter changes the relative path loss is discussed.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Ayberkin, Doruk/0000-0003-3409-8926
Keywords: Wave diffraction; S-UTD-CH model; ray tracing technique; impedance wedge